Thrombospondin-1 in ocular surface health and disease - Foulsham, William (Ocul Surf, 2019)
Thrombospondin 1 (TSP-1) is an extracellular matrix protein that interacts with a wide array of ligands including cell receptors, growth factors, cytokines and proteases to regulate various physiological and pathological processes. Constitutively expressed by certain ocular surface tissues (e.g. corneal and conjunctival epithelium), TSP-1 expression is modulated during ocular surface inflammation. TSP-1 is an important activator of latent TGF-β, serving to promote the immunomodulatory and wound healing functions of TGF-β. Mounting research has deepened our understanding of how TSP-1 expression (and lack thereof) contributes to ocular surface homeostasis and disease. Here, we review current knowledge of the function of TSP-1 in dry eye disease, ocular allergy, angiogenesis/lymphangiogenesis, corneal transplantation, corneal wound healing and infectious keratitis.